TREATMENT OF ADVANCED SYSTEMIC MASTOCYTOSIS WITH MIDOSTAURIN: PRACTICAL GUIDANCE FOR OPTIMAL THERAPY AND MANAGEMENT - Cristina Papayannidis; Vincenzo Federico; Luana Fianchi; Patrizia Pregno; Novella Pugliese; Alessandra Romano; Federica Irene Grifoni (Mediterranean Journal of Hematology and Infectious Diseases)
Systemic mastocytosis (SM) is a rare disease with a range of clinical presentations, and the vast majority of patients have a KIT D816V mutation that results in gain of function. The multikinase/KIT inhibitor midostaurin inhibits the D816V mutant, and has a well-established role in treatment of advanced SM. Even if considered the standard of therapy, some open questions remain on how to optimize the management of midostaurin in daily practice. The current review presents the opinions of a group of experts who met to discuss routine practice with the use of midostaurin in patients with advanced SM. The efficacy and safety of midostaurin in Phase 2 trials are overviewed, followed by practical guidance for optimal management of therapy and adverse events during therapy with midostaurin. Specific guidance is given for initiating therapy and evaluating response with midostaurin in terms of general assessment and laboratory, instrumental, pathological, and molecular exams. Special consideration is given to dose interruption, reduction, and discontinuation of therapy as well as adverse event management and supportive therapy. Patients should be informed about possible side effects and receive not only practical advice to avoid or limit them, but also antiemetic prophylaxis so that therapy with midostaurin can continue as long as clinical benefit is observed or until unacceptable toxicity occurs. Lastly, considerations on the use of midostaurin during the ongoing Covid-19 pandemic are made. The overall scope is to provide guidance that can be useful in daily practice for clinicians using midostaurin to treat patients with advanced SM.